2009
DOI: 10.1677/erc-08-0130
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine improves antitumor effects of docetaxel and cisplatin in aggressive prostate cancer models

Abstract: One of the major obstacles in the treatment of hormone-refractory prostate cancer (HRPC) is the development of chemoresistant tumors. The aim of this study is to evaluate the role of azacitidine as chemosensitizing agent in association with docetaxel (DTX) and cisplatin using two models of aggressive prostate cancer, the 22rv1, and PC3 cell lines. Azacitidine shows antiproliferative effects associated with increased proportion of cells in G0/G1 and evident apoptosis in 22rv1 cells and increased proportion of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…Furthermore, bicalutamide monotherapy is associated with increased expression of ERBB-2 and phosphorylated AKT and reduced expression of PTEN in PCa (5). Interestingly, our work suggests that miR-331-3p has the capacity to block PI3K/AKT signaling in PCa cells independent of their PTEN status (LNCaP, PTEN-negative; 22Rv1 and DU145, PTEN-positive) (50), possibly by targeting other molecules involved in this pathway downstream of PTEN, and thus miR-331-3p could be used to overcome the inherent resistance of PTEN-negative prostate cancers to anti-ERBB-2 and other second line therapies (e.g. chemotherapy).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, bicalutamide monotherapy is associated with increased expression of ERBB-2 and phosphorylated AKT and reduced expression of PTEN in PCa (5). Interestingly, our work suggests that miR-331-3p has the capacity to block PI3K/AKT signaling in PCa cells independent of their PTEN status (LNCaP, PTEN-negative; 22Rv1 and DU145, PTEN-positive) (50), possibly by targeting other molecules involved in this pathway downstream of PTEN, and thus miR-331-3p could be used to overcome the inherent resistance of PTEN-negative prostate cancers to anti-ERBB-2 and other second line therapies (e.g. chemotherapy).…”
Section: Discussionmentioning
confidence: 79%
“…Further studies on this matter are warranted, especially to determine whether demethylating agents could sensitize resistant cells to conventional cytostatic drugs in AML, which has already been shown in vitro in other cancers. 28,29 Furthermore, our analysis showed that global LUMA methylation data were prognostically important mainly in patients younger than 65 years. One explanation for this could be that intra-individual methylation variation accelerates with increasing age, which could affect both global and gene-specific methylation and hence make cross-sectional analyses such as ours less predictive in an older population.…”
Section: Associations Between Methylation Status and Genetic Abnormalmentioning
confidence: 73%
“…Some previous studies have reported on the cellular proliferation inhibitory effect of 5-aza-dCR in PCa cell lines [25][26][27]. In fact, 5-aza-dCR induces p53 and p21Waf1/Cip1 expression which is associated with inhibition of cell proliferation and induction of apoptosis in LNCaP cells, independently of DNA methylation [28,29].…”
Section: Discussionmentioning
confidence: 92%
“…Those studies demonstrated that 5-Aza-dCR could sensitize PCa cell lines to docetaxel, which is the first line therapy for castration-resistant PCa [25]. Likewise, 5-Aza-dCR might restore the expression of androgen receptor in PC-3 cell line, and the combined treatment with bicalutamide demonstrated a synergistic effect in repressing tumor growth in xenograft mice [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation